Learning Strategies for Disaster Mitigation Education at the Elementary School Level: A Systematic Literature Review - Sartika Yolanda; Yunus Abidin; Dede Trie Kurniawan (Didaktika: Jurnal Kependidikan, 2025)
Natural disasters are indiscriminate in their victims; elementary school-aged children are highly vulnerable to these events. However, disaster mitigation education for elementary school students remains scarce, and mitigation efforts in each region have unique characteristics that need to be adapted by educational units in various areas. This research aims to identify learning strategies for disaster mitigation among elementary school students and to determine whether disaster mitigation education needs to be implemented repeatedly by educational units. This research is a Systematic Literature Review conducted by identifying, reviewing, evaluating, and interpreting all available research. The design used in this study involves summarizing, reviewing, and analyzing 10 articles focusing on disaster mitigation in elementary schools, specifically two articles published in Q2 reputable journals and the rest in nationally accredited Sinta journals. These articles were retrieved from online journal databases such as Google Scholar, ResearchGate, SINTA, DOAJ, ERIC, and Scopus. The results of this research indicate that disaster mitigation learning strategies in elementary schools can be implemented using various teaching materials and learning media with visual learning styles, diverse simulation- and practice-based learning models and approaches, tailored to the characteristics of the disaster mitigation material and the age of elementary school students.